Analisis Kelayakan Investasi Mesin Untuk Meningkatkan Kapasitas Produksi (Studi Kasus di CV Djarum Mulia Embroidery Semarang) - Endro Prihastono; Enti Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2015)
CV. Djarum Mulya Embroidery is a company which is engaged in embroidery. At first CV. Djarum Mulya Embroidery has only three pieces of embroidery machine, by increasing their requests for consumer and export demand increasing while the production capacity is no longer sufficient to CV. Djarum Mulya Embroidery will increase the number / capacity of embroidery machine. The company will invest Computer Embroidery Machine Brand SWF 20 Head 9 color 33x55 area at a price of 220 million with the economic life of 5 years. And analysis of investments in the can that the payback period for the investment Computer Embroidery Machine Brand SWF 20 is 1.71 years, this means shorter than the time economical investment of 5 years, Profitability index was 2.24 greater than one, the Net Present Value of Rp. 273 455 696 greater than 0, Internal Rate of Return of 51.47% is greater above the required rate, namely 7.50%. Based on the results of the investment analysis Computer Embroidery Machine Brand SWF 20 who do deserve to be invested. Keywords: Investment, Feasibility